Digital Payment, Support, and Ethics Drive Micro and Small Business Income - Fauzan Najib; Zuhrinal M Nawawi; Khairina Tambunan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid evolution of financial technology has introduced digital payment systems as vital tools for business growth. Specific Background: Within the context of Indonesian micro, small, and medium enterprises (MSMEs), especially in Medan City, these advancements intersect with government policy and religious ethics. Knowledge Gap: However, limited empirical evidence exists on how digital payments, Islamic business principles, and state subsidies collectively influence MSME income. Aims: This study aims to quantitatively examine the effect of digital payment technologies, Islamic business practices, and government subsidies on MSME revenue in Medan. Results: Using a correlational approach and Slovin-based purposive sampling of 100 MSME owners from a population of 70,843, multiple linear regression analysis reveals that all three independent variables significantly and positively affect MSME income. Novelty: The study integrates faith-based economic principles with technological and policy variables, providing a unique multidimensional perspective on MSME growth. Implications: The findings suggest that synergistic support—combining ethical entrepreneurship, digital finance, and government intervention—can enhance income generation for MSMEs, thereby offering valuable policy insights for sustainable economic development. Highlights: Reveals how Islamic principles integrate with modern business tools. Shows digital payments and subsidies boost MSME profits. Offers policy insights for sustainable MSME development. Keywords: Digital Payments, Islamic Business, Government Subsidies, MSME Income